A análise aspectual do present perfect e do pretérito perfeito à luz da teoria de tradução de J. C. Catford - Vanessa Bezerra Maneschy (Cadernos de Tradução, 2007)
This paper explores a translation theory proposed by J. C. Catford, by first of all examining his typology in order to give subsequent emphasis to his relation between translation and meaning. Catford introduces the notion of situational marks, concept in which a comparative study of English and Portuguese will be done in order to verify the existence of common situational marks while analyzing the divergent one, in this case, the verbal system and the grammatical notion of aspect.